Collaboration of Discovery Learning and Lecture Models in Improving PAI Learning Outcomes in The Post-Pandemic Era: Kolaborasi Model Discovery Learning dan Ceramah Dalam Meningkatkan Hasil Belajar PAI di Era Pasca Pandemi - Sukma, Fahiroh (CV. Media Publikasi Profesional, 2023)
This study aims to examine the effectiveness of the collaboration of the Discovery Learning learning model and the lecture method in improving student learning outcomes in Islamic Religious Education (PAI) subjects at SMK Sukma Mandiri after the Covid-19 pandemic. This research was conducted to answer the need for learning adaptation due to decreased student concentration and motivation after the online learning period. The method used was Classroom Action Research with two cycles, collecting data through observation of learning activities, learning outcome tests, and documentation, which were then analysed using descriptive statistical techniques. The research findings showed an increase in student learning completeness from 69.6% in cycle I to 87% in cycle II, indicating that the combination of Discovery Learning and lectures was able to increase learning activities, maintain concentration, and significantly improve student learning outcomes. The implication of this study confirms the importance of learning innovations that combine active and expository methods to face learning challenges in the post-pandemic era, and encourages the development of educational policies based on collaborative approaches. The originality of this research lies in the contextual application of the combination of Discovery Learning and lectures in post-pandemic PAI learning, an approach that has not been widely explored in previous research, thus making a new contribution to pedagogical practices that are adaptive and relevant to the changing characteristics of today's students.